Caffeine ameliorates high energy diet-induced hepatic steatosis: sirtuin 3 acts as a bridge in the lipid metabolism pathway1. Issue 8 (5th August 2015) - Zhang, Shi-Jie; Li, Yi-Fang; Wang, Guo-En; Tan, Rui-Rong; Tsoi, Bun; Mao, Gao-Wei; Zhai, Yu-Jia; Cao, Ling-Fang; Chen, Min; Kurihara, Hiroshi; Wang, Qi; He, Rong-Rong
<x xml:space="preserve">Abstract</x> We demonstrate that caffeine could improve HED-induced hepatic steatosis by promoting lipid metabolism via the cAMP/CREB/SIRT3/AMPK/ACC pathway. SIRT3 acts as a molecular bridge connecting caffeine and lipid metabolism.